Singular and Bright soliton solutions for the coupled system corresponding to Gerdjikov-Ivanov equation with four-wave mixing terms - Altwaty, Abdulmalik (Journal of Pure & Applied Sciences, 2022)
The extended trial function method is utilized in birefringent fibers to generate optical soliton solutions to the coupled system that correspond to the Gerdjikov-Ivanov equation with four-wave mixing terms. The approach yields singular and bright soliton solutions, and in addition extremely important singular and singular periodic soliton solutions are extracted by taken the limit of the modulus of ellipticity of the Jacobi’s elliptic function. The conditions under which the soliton solution exist are also provided.